2015
DOI: 10.1177/0022034515577427
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Tgfbr2 in Odontoblasts Leads to Aberrant Pulp Calcification

Abstract: Transforming growth factor β (TGF-β) signaling has been implicated in dentin formation and repair; however, the molecular mechanisms underlying dentin formation remain unclear. To address the role of TGF-β signaling in dentin formation, we analyzed odontoblast-specific Tgfbr2 conditional knockout mice. The mutant mice had aberrant teeth with thin dysplastic dentin and pulpal obliteration, similar to teeth from human patients with dentinogenesis imperfecta type II and dentin dysplasia. In mutant, the odontoblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…In our cohort, only one patient with LDS1 exhibited a phenotype similar to dentinogenesis imperfecta resulting in the pathognomonic severe grey tooth discolouration. The involvement of TGF-β signalling in dentin development is supported by numerous mouse studies 26 39 40. Dentin is produced by odontoblasts that are part of the dental mesenchyme and are derived from neural crest cells.…”
Section: Discussionmentioning
confidence: 97%
“…In our cohort, only one patient with LDS1 exhibited a phenotype similar to dentinogenesis imperfecta resulting in the pathognomonic severe grey tooth discolouration. The involvement of TGF-β signalling in dentin development is supported by numerous mouse studies 26 39 40. Dentin is produced by odontoblasts that are part of the dental mesenchyme and are derived from neural crest cells.…”
Section: Discussionmentioning
confidence: 97%
“…Further research is necessary to determine which signals and the precise timing required to promote axonogenesis and/or guide the axons to their appropriate targets during tooth innervation. A previous study demonstrated that the conditional deletion of Tgfbr2 in odontoblasts led to disrupted matrix secretion that calcified and obliterated the pulp chamber with age (Ahn et al 2015). This indicated that Tgfbr2 is crucial to maintaining soft pulp tissue, including the neuronal structures contained in it.…”
Section: Discussionmentioning
confidence: 98%
“…Odontoblast-specific disruption of Smad4 using Col1a1 -, Osteocalcin -, and Dspp -Cre resulted in gradual impairment of secondary dentin formation 38 . In addition, disruption of Tgfbr2 in odontoblasts leads to severe impairment of secondary dentin formation with idiopathic pulpal calcification 39 . Similarly, disruption of Bmpr1a in odontoblasts leads to secondary dentin defects without idiopathic pulpal calcification 39 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, disruption of Tgfbr2 in odontoblasts leads to severe impairment of secondary dentin formation with idiopathic pulpal calcification 39 . Similarly, disruption of Bmpr1a in odontoblasts leads to secondary dentin defects without idiopathic pulpal calcification 39 . Both these reports and our results suggest that progerin disturbs critical signaling involved in odontogenesis collectively required for proper secondary dentin formation.…”
Section: Discussionmentioning
confidence: 99%